Exploring EFL High School Student’s Experience in Using VSS In Learning General Vocabulary Through TED-Talk Captioned Video-Assisted: Classroom Action Research. - prakoso, kurniawan aji; Yanto, Elih Sutisna (Peneliti.net, 2024)
Over the years, even though there has been a lot of study on vocabulary learning strategies, the usage of the Vocabulary Self-Collected Strategy integrated with video viewing activity as an approach is still underreported. Therefore, to fill this void, this study aims to find out students experience and their responses in incidental vocabulary learning through video-viewing activities and to what extent the integration of VSS and video viewing help students in learning general vocabulary on high school students in Karawang. In this research, classroom action research is used. The information is collected through observation, interviews, and reflective journals. By examining the result of data from the meeting, the researcher came to the opinion that using VSS to teach vocabulary in combination with a video viewing activity helped the students comprehend the text more easily. By investigating students' responses to general vocabulary learning within VSS and video viewing activity, the current study contributes to the existing literature by providing insights into its potential to improve EFL students' vocabulary mastery.